2015
DOI: 10.1007/s10461-015-1081-3
|View full text |Cite
|
Sign up to set email alerts
|

Pre-exposure Prophylaxis Adherence Measured by Plasma Drug Level in MTN-001: Comparison Between Vaginal Gel and Oral Tablets in Two Geographic Regions

Abstract: Despite strong evidence that daily oral pre-exposure prophylaxis (PrEP) reduces HIV risk, effectiveness across studies has varied. Inconsistent adherence constitutes one explanation. Efforts to examine adherence are limited when they rely on self-reported measures. We examined recent adherence as measured by plasma tenofovir (TFV) concentration in participants of MTN-001, a phase 2 cross-over trial comparing oral tablet and vaginal gel formulations of TFV among 144 HIV-uninfected women at sites in the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
(26 reference statements)
4
10
0
Order By: Relevance
“…This finding is similar to MTN-001, an open-label, cross-over trial of the same products but for a 6-week duration, where adherence estimates differed among US versus African participants, but within sub-Saharan Africa, was similar between products [31]. Among those who behaviourally acknowledged non-use concordance with PK data was very high; however, very few (≤10%) acknowledged low adherence.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This finding is similar to MTN-001, an open-label, cross-over trial of the same products but for a 6-week duration, where adherence estimates differed among US versus African participants, but within sub-Saharan Africa, was similar between products [31]. Among those who behaviourally acknowledged non-use concordance with PK data was very high; however, very few (≤10%) acknowledged low adherence.…”
Section: Discussionsupporting
confidence: 73%
“…In the iPrEx trial, CASI and FTFI provided similarly inflated estimates of pill adherence, and were poor predictors of drug detection, with important variations by geographical areas [24]. Thus, in VOICE, iPrEX, Fem-PrEP and MTN-001 (although the latter two trials did not implement ACASI), findings suggest that over-reporting in the context of low product use was common, at least in non-US settings [24,31,35,36]. Self-reports also appeared greatly overestimated when compared to objective assessments of use in earlier microbicide trials, such as the Carraguard trial [37] or in CAPRISA 004 [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Further, most participants had a history of tampon use, and in other settings, insertion of vaginal products may be less common. Higher product adherence in the United States as compared with Africa was reported for daily vaginal gel and oral tablet in a multisite open-label prevention trial (23), so it is not clear if the high adherence experienced in this study will translate to other settings. Current Phase III trials of the vaginal ring in Africa are using drug biomarkers to assess ring adherence and will provide evidence in the near future as to whether high ring adherence holds its promise with long-term use, sexual activity, and in different populations (12,13).…”
Section: Discussionmentioning
confidence: 83%
“…health care and the reimbursement); a desire for continued access to these benefits may have reduced the likelihood of disclosure of product nonuse at exit, perhaps because participants wanted to be considered for future studies [19]. Unlike U.S. participants in MTN 001, an open label daily-use PrEP trial with TDF tablets and TFV gel, who reported that monetary payments instilled a sense of obligation to use the products [20], the African participants in that study — as in VOICE — did not necessarily operate within the same transactional framework. Rather, the payments may have instilled an obligation on the part of African participants to appear to use the products.…”
Section: Discussionmentioning
confidence: 99%